Flight simulator testing to enhance comprehension and modeling of rotorcraft pilot couplings - Zanoni, A.; Zago, M.; Paolini, R.; Quaranta, G.; Masarati, P.; Galli, M.; Maisano, G.; Frigerio, L.; Murawa, M. (My University, 2019)
The results of a pilot-in-the-loop flight simulator test campaign, aimed at enhancing the comprehension of the interaction between the pilot biomechanical response and the rotorcraft dynamics, are presented. Biomechanical properties - upper limbs motion and electromiographic activities of the most involved muscles - of a test pilot involved in the complex task of ship deck landing, in varying sea conditions and with different helicopter configurations, have been measured. The analysis of the collected data highlights the dependence of the muscular activity on the perceived workload ratings (Bedford scale), and with the approaching of the most challenging portion of the simulated mission, namely the moving deck landing. Several fallbacks on numerical multibody modeling of the biomechanical behavior of the rotorcraft pilot are discussed, in the view of enhancing the quality of prediction of rotorcraft-pilot coupling phenomena.